Comprehensive Essays For World History Finals - Feldman, Martha (Teaching History: A Journal of Methods, 1997)
When formulating final exam questions for world history classes, a dilemma arises: what to do about comprehensive questions. At final exam time there is usually a large block of material over which students have not yet been tested. There is a temptation to cover only that, especially since essay topics in a more limited period seem more manageable for most students. Comprehensive questions can become overwhelming: "Discuss all the wars since 1500." They can be of questionable relationship: "Compare and contrast modernization in England in the 18th century and China in the 20th century." They can be downright trivial: "Plan a dinner party and explain your guest list of the seven most interesting people we have studied this semester." Occasionally inspiration strikes and a wonderfully phrased question elicits thoughtful and thorough responses summing up and expanding on themes of the course from intelligent, motivated students. Perhaps you have had great success with comprehensive questions. I have usually not been very happy with mine, until recently that is, when I hit upon a comprehensive examination question based on current newspaper articles.